The presence of cerebellar B cell aggregates is associated with a specific chemokine profile in the cerebrospinal fluid in a mouse model of multiple sclerosis - Schropp, Verena; Chunder, Rittika; Dietel, Barbara; Tacke, Sabine; Kuerten, Stefanie (Journal of Neuroinflammation, 2023)
Background: The presence of meningeal ectopic lymphoid structures (ELS) in a subgroup of patients diagnosed with secondary progressive multiple sclerosis (SPMS) corresponds to a pronounced cortical inflammation and an aggravated disease course. In MP4-induced experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis (MS), B cell aggregates develop in the central nervous system (CNS) in the chronic stage of the disease. Therefore, the model is suitable for studying key molecules of ELS development and maintenance. Here, we investigated whether there is a specific cytokine and chemokine signature in paired cerebrospinal fluid (CSF) and serum samples associated with the presence of cerebellar B cell and T cell pathology and B cell aggregates of MP4-immunized mice. Methods: Paired CSF and serum samples were collected from the cisterna magna and periphery of MP4-immunized mice at the chronic stage of disease. A control group with mice immunized only with the adjuvant (vehicle) was included in the study. A selected panel of 34 cytokines and chemokines were measured by MAGPIX® for both cohorts. For the assessment of B cell and T cell infiltration, immunohistochemical staining was performed and analyzed using light microscopy. To detect specific chemokine receptors additional staining was conducted. Results: While we detected several upregulated cytokines and chemokines in the CSF of MP4-immunized mice independent of the extent of B cell and T cell pathology compared to vehicle-immunized mice, C-C motif chemokine ligand (CCL)-1 was associated with high B cell and T cell infiltration. Furthermore, the level of certain chemokines, including CCL1, CCL5, CCL7, CCL12, CCL22 and C-X-C motif chemokine ligand (CXCL)-13, was significantly increased (p < 0.05) in MP4-immunized mice showing a high number of B cell aggregates. While C-C motif chemokine receptor (CCR)5 had a ubiquitous expression independent of the extent of B cell and T cell pathology, C-X-C motif chemokine receptor (CXCR)-5 and CXCR6 expression was specifically associated with high B cell and T cell pathology. Conclusion: Our data suggest that multiple cytokines and chemokines are involved in the pathophysiology of MP4-induced EAE. Furthermore, the presence of B cell aggregates was associated with a specific chemokine profile in the CSF, which might be useful for predicting the presence of these aggregates without the necessity to histologically screen the CNS tissue.
CRIS-Team Scopus Importer:2023-02-10
Keywords: B cell aggregates; Chemokines; CSF; EAE; MP4